2017
DOI: 10.1589/jpts.30.27
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between anterior pelvic tilt and gait, balance in patient with chronic stroke

Abstract: [Purpose] The aim of this study is to find out the association between anterior pelvic tilt and gait and balance in chronic stroke. [Subjects and Methods] Fourteen chronic stroke patients were included in this study. A palpation meter was employed to measure the anterior inclination of the pelvis. A GAITRite system automates measuring temporal and spatial gait parameters. A 10-Meter Walk test was used to measure gait speed. The Timed Up and Go test was used to measure the dynamic balance ability and gait abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Previous studies reported that stroke patients exhibit low temporal synchronization between the pelvis and lower extremities when walking or performing functional postures and showed anterior pelvic tilt with impaired motor function [5,6]. Moreover, Kim et al confirmed that the anterior pelvic tilt in stroke patients had significant negative correlations with gait velocity, cadence, and step length [22]. In addition, in stroke patients, weakening of the hip extensor, which is most involved in the terminal stance of the gait, affects the movement control of the hip and knee flexion during the ipsilateral swing phase, resulting in a decrease in walking speed [33,34].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Previous studies reported that stroke patients exhibit low temporal synchronization between the pelvis and lower extremities when walking or performing functional postures and showed anterior pelvic tilt with impaired motor function [5,6]. Moreover, Kim et al confirmed that the anterior pelvic tilt in stroke patients had significant negative correlations with gait velocity, cadence, and step length [22]. In addition, in stroke patients, weakening of the hip extensor, which is most involved in the terminal stance of the gait, affects the movement control of the hip and knee flexion during the ipsilateral swing phase, resulting in a decrease in walking speed [33,34].…”
Section: Discussionmentioning
confidence: 93%
“…Since the trunk is bilaterally innervated and connected by the linea alba with fascia, damage to one side of the brain affects all of the abdominal muscles, which in turn affects the position of the anterior superior iliac spines [9]. The normal anterior pelvic tilt angle was reported as 11 ± 4 • [22][23][24]. In this study, a stroke patient with a pelvic anterior tilt angle of 15 • or more was targeted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of stationary systems to measure gait function, such as the GAITRite system or 3D camera-based systems, have been shown to be quite effective, and previous work using these approaches have also reported efficacy in quantifying gait in many research and rehabilitation settings [1,10,11,12,13,14,15,16]. These approaches have also been used to evaluate gait in healthy controls, with similar values in gait measurements observed to that in the present study [1,10].…”
Section: Discussionmentioning
confidence: 99%
“…Each subject completes the sequence 3 times, and the amount of time required for each sequence is measured and the average of the three is recorded. Bio-rescue showed good inter-rater and intra-rater reliability in measurements during footprint area (Kim et al, 2018).…”
Section: Methodsmentioning
confidence: 99%